A novel HLA‐A*02 allele, A*02:543 was identified by polymerase chain reaction sequence‐based typing in a Chinese cord blood donor. (18th March 2016) - Dong, L.‐N.; Chen, N.‐Y.; Zhang, W.; He, J.; Zhu, F.‐M.
Abstract : HLA‐A*02:543 differ from HLA‐A*02:12 by two nucleotide substitutions.